Nanoparticulate Antibiotic Systems as Antibacterial Agents and Antibiotic Delivery Platforms to Fight Infections. (12th September 2020) - Vassallo, Antonio; Silletti, Maria Francesca; Faraone, Immacolata; Milella, Luigi
Abstract : Today's human society, product of decades of progress in all fields of knowledge, would have been unimaginable without the discovery of antibiotics and more generally of antimicrobials. However, from the beginning, the scientific community was aware that microorganisms through various strategies were able to hinder and render vain antibiotic action. Common examples are the phenomena of persistence, tolerance, and resistance, up to the creation of the feared bacterial biofilms. Antibiotics are a precious but equally labile resource that must be preserved but at the same time reinforced to safeguard their effectiveness. Nanoparticulate systems such as nanobactericides, with their inherent antibacterial activity, and nanocarriers, which operate as drug delivery systems for conventional antibiotics, are innovative therapies made available by nanotechnology. Inorganic nanoparticles are effective both as nanobactericides (AgNPs, ZnONPs, and TiO2 NPs) and as nanocarriers (AgNPs, AuNPs, ZnONPs, and TiO2 NPs) against sensitive and multi-drug-resistant bacterial strains. Liposomes are among the most studied and flexible antibiotic delivery platforms: conventional liposomes allow passive targeting at the mononuclear phagocytic system (MPS); "stealth" liposomes prevent macrophage uptake so as to eradicate infections in tissues and organs outside MPS; thanks to their positive charge, cationic liposomes interact preferentially with bacterial and biofilm surfaces, acting as innate antibacterials as well as drug delivery systems (DDS); fusogenic liposomes have fluid bilayers that promote fusion with microbial membranes; and finally, ligand-targeted liposomes provide active targeting at infection sites. Dendrimers are among the most recent and attractive nanoparticulate systems, thanks to their multibranched nanoarchitecture, which equipped them with multiple active sites for loading antibiotics and also interacting with bacteria. Finally, nanoantibiotics represent a new hopeful generation of antibiotic candidates capable of increasing or even restoring the clinical efficacy of "old" antibiotics rendered useless by the resistance phenomena.